EXPLORING STUDENTS’ STRATEGIES AND METHODS IN TRANSLATING INDONESIA-ENGLISH TEXT - Ayu Rizki Septiana (LinguA-LiterA: Journal of English Language Teaching Learning and Literature, 2020)
This research was aimed to explore the strategies and methods used by the students in translating Indonesian text into English. Descriptive qualitative was used as the research design. Further, the data were taken in two methods, that is, translation test and questionnaire. Since it was done during the pandemic of Covid-19 in which the students should learning from home, the translation test as well as the questionnaire were done online using the Google Classroom and the Google Form. The result showed that the students mostly used through translation and shift of translation as the strategies to translate Indonesia-English text. While for the method, the students mostly used the free translation so that they were not tied with the structure of target language. However, it is suggested for the translators to mind on the grammatical structure of both texts, cultural words, and writing mechanic. Further, the translators should also pay attention on the similarities and differences of the structure of source language and target language. As additional data, the questionnaire result showed that the students usually used translation machine like Google translate as their helping tools. Moreover, it is known from the result of the questionnaire, the students usually found difficulties in using appropriate strategies and methods of translation, finding the equivalences of words in target language, lack of knowledge on the field of translation as well as lack of time to practice their translation skill.